Atypical Testicular Torsion Due to an Epididymal Cyst in a Young Adult: Case Report - Wa Numbe BC; Mukamba FM; Musilimu CS; Rudahaba Nshengo J; Muhindo Busamba L; Mirindi DC; Mubenga Mukengeshai LE (Research and Reports in Urology)
Bachelard Cissa Wa Numbe,1,2 Franck Masumbuko Mukamba,1,2 Costa Sudi Musilimu,1,2 Joelle Rudahaba Nshengo,1,2 Lievin Muhindo Busamba,1,2 Dominique Chimanuka Mirindi,1,2 Léon-Emmanuel Mubenga Mukengeshai1– 3 1Faculty of Medicine, Université Catholique de Bukavu (UCB), Bukavu, Democratic Republic of Congo; 2Department of Surgery, Hôpital Provincial Général de Référence de Bukavu (HPGRB), Bukavu, Democratic Republic of Congo; 3Institut supérieur des techniques médicales de Bukavu (ISTM Bukavu), Bukavu, Democratic Republic of CongoCorrespondence: Bachelard Cissa Wa Numbe, Email wcissa1@gmail.comBackground: Acute scrotal pain is a urological emergency. Testicular torsion (TT) is a surgical emergency that compromises rapidly testicular viability. There is approximately a 4- to 8-hour window from the onset of torsion symptoms until surgical intervention is required to save the affected testis. Delays in care may necessitate orchiectomy, which has been associated with reduced fertility. It can occur at any age, with two peaks of frequency: during the first years of life and at puberty. The causes of testicular torsion are multiple and are related to a defect in the fixation system of the testicle.Case Presentation: Here we report an unusual situation of testicular torsion induced by a large epididymal cyst in a young adult. The cyst was excised as well as bilateral testicular fixation and the patient was discharged on the third day. Clinical examinations and Doppler ultrasound at the sixth and twelfth postoperative weeks were both normal.Conclusion: This observation leads us to consider epididymal cysts as a risk factor for TT.Keywords: atypical, testicular, torsion, epididymal cyst, young adult